C-reactive protein to albumin ratio in Behçet’s disease - Ünal Enginar, Ayşe (The European Research Journal, 2022)
Objectives: This study aims to evaluate the relationship between C-reactive protein (CRP)/albumin ratio (CAR) and other hematological parameters in Behçet’s disease (BD). Methods: A total of 200 participants (100 BD patients and 100 healthy control) were recruited from the rheumatology outpatient clinic in this cross-sectional study. Laboratory tests were conducted to measure complete blood count, erythrocyte sedimentation rate (ESR), CRP, albumin, CAR, neutrophil to lymphocyte ratio (NLR), and platelet to lymphocyte ratio (PLR). Laboratory findings of BD patients and healthy controls were compared and evaluated. BD Activity scores (Behçet’s Disease Current Activity Form [BDCAF]) were calculated. Results: In the BD group, there were 42 male and 58 female participants with a mean age of 42.49 ± 13.15 years and in the healthy control group, 44 male and 56 female participants with a mean age of 44.90 ± 10.98 years. NLR, CRP, ESR and CAR values were significantly higher in patient group than in the healthy controls (p < 0.05). BDCAF score varied between 0 and 4 with a mean of 1.55 ± 0.64. A statistically significant correlation was observed between BDCAF and CRP, ESR and CAR (p < 0.0001). Conclusions: In this study, a significant correlation was found between CAR and BDCAF, NLR, CRP, albumin and ESR. CAR can be useful in the diagnosis and following of BD patients.